Scaling maximal oxygen uptake to predict performance in elite-standard men cross-country skiers - Carlsson, T.; Carlsson, M.; Fellekid, M.; Hammarström, D.; Heile, D.; Malm, C.; Tonkonogi, M. (Journal of Sports Sciences, 2013)
The purpose of this study was to: 1) establish the optimal body-mass exponent for maximal oxygen uptake (O2max) to indicate performance in elite-standard men cross-country skiers; and 2) evaluate the influence of course inclination on the body-mass exponent. Twelve elite-standard men skiers completed an incremental treadmill roller-skiing test to determine O2max and performance data came from the 2008 Swedish National Championship 15-km classic-technique race. Log-transformation of power-function models was used to predict skiing speeds. The optimal models were found to be: Race speed = 7.86 · O2max · m-0.48 and Section speed = 5.96 · O2max · m-(0.38 + 0.03 · a) · e-0.003 · Delta (where m is body mass, a is the section`s inclination and Delta is the altitude difference of the previous section), that explained 68% and 84% of the variance in skiing speed, respectively. A body-mass exponent of 0.48 (95% confidence interval: 0.19 to 0.77) best described O2max as an indicator of performance in elite-standard men skiers. The confidence interval did not support the use of either "1" (simple ratio-standard scaled) or "0" (absolute expression) as body-mass exponents for expressing O2max as an indicator of performance. Moreover, results suggest that course inclination increases the body-mass exponent for O2max.